Multivariate analysis of organic contaminants in groundwater of an endorheic basin draining to a salt lagoon – Fuente de Piedra (Southern Spain) - Llamas Dios, Marta Inés; Jiménez-Gavilán, Pablo; Corada Fernández, Carmen; Ojeda, Lucía; Jiménez Martínez, Juan Francisco; Vadillo-Pérez, Iñaki (Elsevier, 2024)
Forthcoming EU environmental requirements on water resources quality are likely to include concentration limits of certain contaminants of emerging concern, such as pharmaceuticals and personal care products. However, understanding the occurrence of organic contaminants, including contaminants of emerging concern, in hydro(geo)logical media remains challenging. This study is based on a comprehensive screening of OCs in groundwater of the unique and complex Fuente de Piedra Lagoon endorheic basin system using hydrochemistry and isotopic tools. The basin includes interconnected aquifers of various types (detrital, carbonate and evaporitic). Groundwater recharges the hypersaline lagoon, which holds significant ecological value, but is heavily impacted by anthropogenic activities such as water exploitation for urban supply and irrigation, soil fertilization for agricultural activities and urban wastewater discharges. Out of 185 analyzed compounds, 32 were detected, including 6 personal care products, 10 antibiotics and 11 pharmaceuticals. Concentrations ranged from 0.1 ng/L to 974 ng/L. Notably, the pesticide aldrin was detected with a maximum concentration of 668 ng/L. Two main processes are suggested as potentially affecting the occurrence of different groups of organic contaminants: (i) re-concentration of the more mobile compounds due to irrigation return flows in the unconfined detrital aquifer and (ii) accumulation of certain contaminants in the deep, saline underground media within the evaporitic aquifer, which forms the geologic basement of the detrital and carbonate aquifers of the basin. This study highlights the difficulty in understanding the occurrence of organic contaminants in complex systems and underscores the challenge of meeting the forthcoming environmental requirements.
Keywords: Agua subterránea; Contaminantes orgánicos del agua; Hidroquímica; Ecología; Hydrochemistry; Overexploitation; Organic contaminants; Emerging contaminants; Groundwater